NEGOTIATING NUTRITION KNOWLEDGE AND PARENTING PRACTICES IN RURAL FAMILIES: A CASE STUDY OF STUNTING IN KEPAHIANG REGENCY - Safitra, Linda; Angraini, Wulan (Sosiohumaniora, 2026)
Stunting remains a serious problem in human development as it affects children’s growth and development and has long-term implications for the quality of human resources. Various efforts to address stunting have generally emphasized health interventions and the dissemination of nutritional information; however, these approaches often overlook family dynamics as the main arena for parenting decision-making. This study aims to analyze how nutrition knowledge is negotiated in parenting practices among rural families with stunting cases in Kepahiang Regency. This study employs a qualitative approach with a case study design. The informants consisted of 16 participants, including mothers of stunted children under five, husbands, children who are able to communicate their preferences, and supporting local actors such as village midwives, members of the Stunting Task Force, and village officials. Data were collected through in-depth interviews and observations and analyzed using thematic analysis. The findings show that nutrition knowledge within families is derived from multiple sources and is not applied linearly, but is continuously renegotiated in accordance with socio-economic conditions, family relations, and everyday parenting practices. Parenting practices are shaped through a negotiation process involving mothers, other family members, and interactions with local institutional actors. This study contributes to the literature by conceptualizing nutrition knowledge as a negotiated social process embedded in rural family dynamics. It concludes that stunting prevention efforts need to position families as active subjects, with approaches that are sensitive to social, economic, and cultural contexts in rural settings.